Study on Importance of Emotional Intelligence in Conflict Management: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper studied the importance of emotional intelligence in conflict management. Conflict is not by nature good or bad. It simply means a difference of opinion or interests. It is also an inevitable occurrence in any workplace. Conflicts can occur because co-workers bring with them differing perspectives and backgrounds, or in some cases, because employees have unclear expectations of their responsibilities. Poor communication is a major contributor to conflict. This can include reading body language, failure to share information, or receiving